Daylight performance in the adjoining spaces of vertical top-lit atrium in the tropics - Mohsen Ghasemi, 1980-, author; Mohd. Zin Kandar, supervisor; Fakulti Alam Bina (2015)
Thesis (Ph.D (Senibina)) - Universiti Teknologi Malaysia, 2015